«Antaviana»: del text narratiu al text dramàtic - Gregori, Carme (Caplletra. Revista Internacional de Filologia, 2015)
The author studies the changes taken place in the stories which have given rise to the theatrical play in its passage from the genres of narrative to drama, from narrated history to performed history.